(untitled) (Bangladesh Journal of Infectious Diseases, 2020)
SARS CoV2 infects the people worldwide and causes a disease named Covid19. It has been first discovered in Wuhan city of central China. Chinese people are presented with severe lung inflammatory pneumonia. No definite cause of their disease could be found, or they could not be cured by conventional anti-viral treatment. The market shoppers and buyers are infected at first through the evolution of any animal sold in the wholesale market of Huanan seafood in Wuhan city. Later, Chinese scientists are able to detect this new type of coronavirus through lab tests. SARS CoV2 has been first transmitted from animals to humans, it is currently able to transmit from human to human. So far, no specific medicine or vaccine has been developed for the disease; therefore, there is no way to cure the disease without intensive treatment at the hospital. This narrative review is written based on SARS CoV2 viral infection. Bangladesh Journal of Infectious Diseases, April 2020; 7(Suppl_1):S32-S35